Pregnancy outcome of freeze thaw cycles of polycystic ovary syndrome patients regarding the anti-Müllerian hormone percentile. (4th July 2022) - Arslanca, Tufan; Ecemis, Tolga; Kiseli, Mine; Arslanoglu, Esra; Kotanoğlu, Mustafa S.; Caglar, Gamze S.
Abstract: Patients with polycystic ovary syndrome display increased levels of anti-Müllerian hormone. Frozen-thawed embryo transfer (FET) prevents ovarian hyperstimulation and results in better pregnancy outcome in PCOS patients. Therefore, we aimed to evaluate the effect of serum AMH levels on the pregnancy outcome of FET cycles in PCOS patients. 110 infertile women with PCOS who were recommended for embryo cryopreservation followed by FET. The patients' AMH levels were evaluated, and the age-related AMH percentiles were determined. The patients were then grouped according to AMH percentiles, namely, 75th–90th percentile (Group 1) and higher than the 90th percentile (Group 2). A total of 110 PCOS patients who conceived in Frozen Embryo Transfer (FET)-In-vitro Fertilisation (IVF) cycles were included in this study. The preterm delivery rates in FET cycles were higher in the group of PCOS patients with AMH levels greater than the 90th percentile than in patients in the 75th–90th percentile group (50% vs 28.8%, p  = .024). In conclusion, PCOS patients with AMH levels higher than the 90 th percentile had substantially higher preterm delivery rates than those with AMH levels at the 75 th –90 th percentile, suggesting the need for closer follow-up. Further studies are needed to elucidate the underlying mechanisms behind this correlation. IMPACT STATEMENT: What is already known on this subject? The association of AMH levels with the risk of adverse pregnancy outcomes has been previously investigated. In women with PCOS, substantially elevated AMH levels were significantly associated with preterm birth. What do the results of this study add? Results showed that the PCOS patients with higher AMH levels and underwent assisted reproductive treatment demonstrated an increased risk of preterm labour than the PCOS patients with lower AMH levels. What are the implications of these findings for clinical practice and/or further research? In women with PCOS, substantially elevated AMH levels were significantly related to preterm birth, suggesting the need for closer follow-up in this population and the need for further studies to elucidate the underlying mechanisms behind this correlation.